A guidance approach for the encouraging classroom - Gartrell, Daniel (Wadsworth Cengage Learning, 2014)
Laying the basis for the guidance approach, this edition links the well respected and innovative theories about child development and developmentally appropriate practice with principles and practices of guidance for the preschool through primary grade age group